Should We Train the Trainers? Results of a Randomized Trial - Murphy, M; Neequaye, S; Kreckler, S; Hands, L (2008)
Background: The development of efficient training methods in surgery is increasingly important. The effectiveness of training trainers is unclear. This study was designed to determine the effect on their trainees' performance of instructing trainers in a specific cognitive training method. Study Design: Ten trainers from a university teaching hospital were randomized to train novices on a one-to-one basis in a simulated procedure using either a four-step cognitive method or their own unspecified method. Thirty trainees were randomly assigned to either a cognitive or standard trainer. After training, trainees were assessed on performing the procedure using a task-specific checklist, a global rating scale, and time taken to complete the procedure. Results: Trainees who were trained using the specific cognitive method completed the procedure in a faster time (mean 331 seconds [SD 37 seconds] versus 426 seconds [SD 66 seconds]) and with higher global rating scores (mean 23.25 seconds [SD 3.7 seconds] versus 20.5 seconds [SD 4.5 seconds]) compared with those taught by a standard method. Conclusions: Instructing trainers in a cognitive training method results in a significant improvement in training outcomes. © 2008 American College of Surgeons.